Evaluation of negative stains for single particle analysis in electron microscopy - Ďurinová, Eva (Jihočeská univerzita, 2018)
Four negative stains, hafnium chloride and europium, samarium and gadolinium nitrates, were tested in single particle electron microscopy as potential alternatives to uranyl acetate, which is recently being widely restricted for its toxicity. The new stains were applied to a structurally well-described plant photosystem I, visualized by a transmission electron microscope and classified in a single particle analysis. The quality of the stains was evaluated by the obtained resolution and ability to provide reliable structural information.
Evaluation of negative stains for single particle analysis in electron microscopy
Keywords: Uranyl acetate; lanthanides; negative staining; single particle analysis; electron microscopy